Driving agricultural evolution: implementing agriculture 4.0 with Raspberry Pi and internet of things in Morocco - Mouachi, Raja; Youssef, Elbelghiti; El mrini, Sanaa; Ezzini, Mustapha; Raoufi, Mustapha (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
The purpose of this project was to investigate the use of embedded system and smartphone technologies in conjunction with Raspberry Pi and NodeMCU to create an intelligent system for smart farming (SF). By means of experiments and comparative analysis carried out in several agricultural contexts, the research evaluated the efficacy of the intelligent system. Results showed that the system was able to handle pertinent agricultural activities and effectively monitor important environmental factors including temperature, humidity, soil moisture, and climatic quality. The system's remote accessibility helped farmers by allowing them to effectively oversee agricultural operations at any time and from any location. As a consequence, SF techniques produced more production, lower costs, and maintained assets.